Contruction of underground subway for Outram Park Mass Rapid Transit station - Chinniah, Ravindran. (2008)
The North East Line (NEL) of MRT tunnels cross under the existing, operational MRT East-West line at Outram Park station. The new construction involves forming the NEL station with in the 2nd reserve zone of railway protection, excavation approximately 8 to llm from the operational tunnels. The station excavation is 18m to 29m deep, and NEL tunnels are constructed approximately llm below the operational tunnels. Majority of the excavation is carried out in predominantly highly and moderately weathered sedimentary rocks of the Jurong Formation.